Applicability of the European Society of Cardiology guidelines on management of acute coronary syndromes to people with haemophilia – an assessment by the ADVANCE Working Group. (28th May 2013) - Staritz, P.; de Moerloose, P.; Schutgens, R.; Dolan, G.; ,
Summary: There are no evidence‐based guidelines for antithrombotic management in people with haemophilia (PWH) presenting with acute coronary syndrome (ACS). The aim of the study was to review the current European Society of Cardiology guidelines, and to consider how best they should be adapted for PWH. Structured communication techniques based on a Delphi‐like methodology were used to achieve expert consensus on key aspects of clinical management. The main final statements are as follows: (i) ACS and myocardial revascularization should be managed promptly by a multidisciplinary team that includes a haemophilia expert, (ii) each comprehensive care centre for adult PWH should have a formal clinical referral pathway with a cardiology centre with an emergency unit and 24 h availability of percutaneous coronary intervention (PCI), (iii) PCI should be performed as soon as possible under adequate clotting factor protection, (iv) bare metal stents are preferred to drug‐eluting stents, (v) anticoagulants should only be used in PWH after replacement therapy, (vi) minimum trough levels should not fall below 5–15% in PWH on dual antiplatelet therapy, (vii) the duration of dual antiplatelet therapy after ACS and PCI should be limited to a minimum, (viii) the use of GPIIb‐IIIa inhibitors is not recommended in PWH other than in exceptional circumstances, (ix) the use of fibrinolysis may be justified in PWH when primary PCI (within 90 min) is not available ideally under adequate clotting factor management. It is hoped that the results of this initiative will help to guide optimal management of ACS in PWH.